EFFICIENCY MACHINING PROGRAM BY COMPARING NUMERICAL CODE CONTROL MADE FROM CATIA AND MASTERCAM - Widodo, Eko Muh. (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2017)
AbstractÂ AbstractTooling department is the department which is engaged in manufacturing of dies that is making a molding tool to create a component / pressed parts made in accordance with the desired design and processed on a press machine, dies ordered from the customer is the sole agent for the brand (car manufacturers). Manufacturing of dies including project work, one of the project, namely the project of manufacturing dies 640A dies drawing part number 53711/12. The project, which is now run already efficient, but to improve services to car manufacturers and to lower the cost of manufacturing the dies on the project it is necessary to compare the code in order to produce a numerical control machining program efficiency. The measures focused on the machining process because there are inefficiencies in the machining program code. Therefore, it will do the analysis of the technical terms in order to get an efficient machining program, so it can reduce the operational costs of the project 640A 53711/12 drawing process. Numerical control (NC) or machining of the program comes from Catia software and MASTERCAM. Numerical control resulting from more effective MASTERCAM machining program for the data that appears in accordance with the dies face (G01: data flat, G02 / G03: Data radius) and therefore contributes to machining machine age. The results of the analysis techniques that select programming from the machining MASTERCAM because it is more effective and calculate the percentage efficiency of the machining program MASTERCAM when compared with catia amounted to 49.36%.